PENGGUNAAN VARIASI BAHASA INDONESIA OLEH MAHASISWA SEMESTER V PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS NEGERI MANADO - Nada, Anwar (Jurnal GeoCivic, 2024)
The main function of language is to communicate. Communication is carried out by humans who are social creatures. Humans as social creatures are always required to interact with other humans. Humans are creatures created to live in contact with other people. The interaction process requires tools to communicate with other individuals. On the basis of this, what is called language variation then emerged.Language variation itself arises because of the social interaction process of various language actors. Language is one of the ghost tools to interact with other humans. All ideas, ideas, and intentions of the speaker are conveyed through language. The characteristics of language variation that occur due to differences in usage include lexicogrammatical, phonological, indicator features in the form of certain word forms, certain grammatical markers, or even phonological markers that function to give signs to language actors that this is the intended register. These markers or characteristics also distinguish one register from another.Language variations regarding their use, usage, or function are called functionalolects. These variations usually discuss the use of style, or level of formality, and means of use. The language variations used vary according to the needs and requirements in their respective fields. For example in the fields of literature, education, military, journalism, economics, trade, and others.